The Urgency of Establishing Special Regulations on Crypto Mining in the Framework of Legal Certainty in Indonesia - Situmeang, Ojak; Soesatyo, Bambang (Greenation Publisher & Yayasan Global Resarch National, 2025)
The rapid development of blockchain technology has driven increased crypto-mining activities in various countries, including Indonesia. However, until now, Indonesia has not had specific regulations that explicitly regulate crypto mining, both in terms of legality, licensing, legal protection, and its impact on the environment and the national electricity system. This ambiguity creates legal uncertainty for business actors, investors, and law enforcement officers in assessing and handling these activities. This study aims to examine the urgency of establishing special regulations regarding crypto mining to provide clear and comprehensive legal certainty. The method used is a normative legal approach with an analysis of applicable laws and regulations and comparative studies with several countries. The study results reveal that special regulations are needed to address the legal challenges that arise from the practice of crypto mining that continues to grow in this digital era.